A Numerical Investigation on Natural Convection Heat Transfer in Annular-Finned Concentric Horizontal Annulus Using Nanofluids: A Parametric Study. Issue 22 (23rd September 2021) - Ashouri, Mahyar; Zarei, Mohammad Mehdi; Hakkaki-Fard, Ali
Abstract: Natural convection heat transfer in a concentric horizontal annulus with annular fins is numerically studied. Due to the low thermal conductivity of water, CuO-water and Al2 O3 -water nanofluids were used as heat transfer fluids. The effect of three different parameters, including fin spacing, fin eccentricity, and fin thickness at different fin diameters and Rayleigh number range of 10 4 to 9  ×  10 5, were studied. The obtained results revealed that Al2 O3 -water nanofluid has the highest heat transfer rate. The calculated heat transfer rates for Al2 O3 -water nanofluid for Rayleigh numbers of 9  ×  10 5, 10 5, and 10 4 were respectively up to 12.1%, 26.2%, and 31.6% higher than the heat transfer rate obtained for water. The best heat transfer rate occurred at the fin spacing range of 2 to 3 mm at Rayleigh number of 9  ×  10 5 . Moreover, it was observed that by decreasing the Rayleigh number, the maximum heat transfer rate took place at higher fin spacing. It was concluded that fin eccentricity improves the heat transfer rate, especially for low fin spacing. Furthermore, it was demonstrated that fin eccentricity could improve the heat transfer rate by up to 50.2%. Simulation results indicated that fins with low thickness have higher heat transfer rates than those with higher thickness at lower fin spacing. However, fins with high thickness have higher heat transfer rates than those with lower thickness at higher fin spacing.